Triatomine Fauna and Recent Epidemiological Dynamics of Chagas Disease in an Endemic Area of Northeast Brazil - Cláudia M. Melo; Ana Carla F. G. Cruz; Antônio Fernando V. A. Lima; Luan R. Silva; Rubens R. Madi; Veronica de Lourdes S. Jeraldo; Ruben Mercado (Canadian Journal of Infectious Diseases and Medical Microbiology)
Updated information of the dispersion dynamics of Chagas disease (CD) and a systemic analysis of these data will aid the early identification of areas that are vulnerable to transmission and enable efficient intervention. This work synthesized spatiotemporal information regarding triatomine fauna and analyzed this information in combination with the results from serological tests to elucidate the epidemiological panorama of CD in the state of Sergipe, Brazil. This is a retrospective analytical study that utilized information from the database of the National Chagas Disease Control Program. Between 2010 and 2016, 838 triatomines of eight species, namely, Panstrongylus geniculatus, which was first recorded in the state of Sergipe, Panstrongylus lutzi, P. megistus, Triatoma brasiliensis, T. pseudomaculata, T. tibiamaculata, T. melanocephala, and Rhodnius neglectus, were collected. Optical microscopy revealed that 13.2% of triatomines examined were infected by Trypanosoma cruzi-like flagellates. The distribution of triatomines exhibits an expanding south-central to northern dispersion, with a preference for semiarid and agreste areas and occasional observations in humid coastal areas due to anthropogenic actions reflected in the environment. Of the human cases analyzed from 2012 to 2016, 8.3% (191/2316) presented positive serology for Trypanosoma cruzi, and this proportion showed a gradual increase in the southern center of the state and new notifications in coastal regions. There is a need for intensification and continuity of the measures adopted by the Chagas Disease Control Program in Sergipe, identifying new priority areas for intervention and preferential ecotopes of the vectors, considering the occurrence of positive triatomines intradomicilliary and a source of new triatomines in the peridomiciles.